2019
DOI: 10.1093/humrep/dez229
|View full text |Cite|
|
Sign up to set email alerts
|

Preimplantation genetic testing for aneuploidy: a comparison of live birth rates in patients with recurrent pregnancy loss due to embryonic aneuploidy or recurrent implantation failure

Abstract: STUDY QUESTION Can preimplantation genetic testing for aneuploidy (PGT-A) improve the live birth rate and reduce the miscarriage rate in patients with recurrent pregnancy loss (RPL) caused by an abnormal embryonic karyotype and recurrent implantation failure (RIF)? SUMMARY ANSWER PGT-A could not improve the live births per patient nor reduce the rate of miscarriage, in both groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(59 citation statements)
references
References 30 publications
2
53
2
2
Order By: Relevance
“…Sato et al showed that PGT-A could improve live birth rate per IVF transfer in RPL cases with history of POC aneuploidy. 43 Zhou et al found no improvement with the use of PGT-A in terms of live birth rate or the rate of miscarriage for women younger than 38 years without recurrent pregnancy loss but with a history of POC with embryonic chromosomal abnormalities. 44 …”
Section: Types Of Genetic Testingmentioning
confidence: 99%
“…Sato et al showed that PGT-A could improve live birth rate per IVF transfer in RPL cases with history of POC aneuploidy. 43 Zhou et al found no improvement with the use of PGT-A in terms of live birth rate or the rate of miscarriage for women younger than 38 years without recurrent pregnancy loss but with a history of POC with embryonic chromosomal abnormalities. 44 …”
Section: Types Of Genetic Testingmentioning
confidence: 99%
“…No significant differences in LB and miscarriage rates per patient given or not given PGT-A were evidenced by Sato et al [94]: 26.8 versus 21.1% and 14.3% versus 20.0%, respectively. Live birth rate per embryo transfer was improved by the application of PGT-A (52.4 vs. 21.6%), which also had the advantage of reducing the number of embryo transfers that are required to achieve a similar number of live births as compared with cycles in which PGT was not performed.…”
Section: Recurrent Pregnancy Lossmentioning
confidence: 75%
“…В исследовании T. Sato и соавт. (2019) [17] супружеским парам с привычным выкидышем в анамнезе проводили ЭКО…”
Section: преимплантационное генетическое тестирование на анеуплоидииunclassified